ANALYSIS OF THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN ENHANCING STUDENTS' LEARNING MOTIVATION AT SMP ADVENT TONDANO - Allen Ch. Manongko; Ayu Elisabeth Butarbutar; Jety D.Lempas (J-Shelves of Indragiri (JSI), 2025)
This study explores the use of Artificial Intelligence (AI) in enhancing students’ learning motivation at SMP Advent Tondano. Using a qualitative descriptive approach, interviews were conducted with five informants, including the Principal, two teachers, and two students, to examine the implementation, benefits, and challenges of AI-based learning. The findings indicate that AI contributes positively to students’ motivation by providing interactive, adaptive, and personalized learning experiences. Features such as real-time feedback, adaptive practice modules, and personalized materials foster greater engagement, curiosity, and independent learning. Both teachers and students highlighted that AI makes learning more enjoyable, challenging, and efficient. However, challenges such as limited devices, unstable internet connections, and varying digital literacy require strategic interventions, including teacher guidance and training. The study concludes that AI, when effectively integrated into classroom instruction, has significant potential to improve learning motivation and outcomes.